Hiccups triggered by bladder filling after bilateral pontine hemorrhage: A case report - Chon, Jinmann (Medicine (Baltimore), 2020)
INTRODUCTION: A hiccup is myoclonus of a sudden involuntary contraction of the diaphragm. Hiccups have various causes, and brain stem stroke is one of the causes of central hiccups. Certain types of hiccups are caused by diseases that can be fatal. Therefore, it is beneficial for physicians to be familiar with the various cases of unusual hiccups. We report a case of hiccups triggered by urinary bladder filling in a brain stem stroke patient. To the best of our knowledge, previous reports have not described a similar case. PATIENT CONCERNS: We describe the case of a 54-year-old patient who had acute bilateral pontine hemorrhage. The patient had intermittent hiccups in the early stages of the stroke onset. The hiccups ceased by the administration of medication or stimulation of the pharyngeal or tracheal wall. Two months after the onset, the Foley catheter was removed to check if the patient could void the bladder voluntarily. Hiccups occurred whenever the bladder was filled with some amount of urine. DIAGNOSIS: Pontine hemorrhage, neurogenic bladder, and quadriplegia. INTERVENTIONS: When the hiccups occurred, the amount of urine in the bladder was checked using a transabdominal bladder ultrasonography scanner. After clean intermittent catheterization for bladder emptying, the hiccups subsided. OUTCOMES: The hiccups occurred 5 or 6 times a day, as often as the bladder was filling. He was unable to void the urine voluntarily for 5 days after the removal of the Foley catheter. Percutaneous suprapubic cystostomy was performed finally to remove the stimulation of bladder filling and the hiccups disappeared. CONCLUSION: Bladder filling is suspected to increase the sympathetic tone and cause a hiccup reflex. Bladder filling could be a factor triggering hiccups in pontine hemorrhage.